Adaptasi Tradisi Pembelajaran Kitab Dayah dalam Pendidikan Islam Formal - Yusba Alhamda Syari (Raudhatun Najah Publisher, 2025)
The transformation of kitab-based learning traditions from dayah into formal schooling raises a critical question regarding how deeply rooted religious values can be sustained within a structured and institutionalized educational system. This study seeks to examine how such transformation unfolds and how it shapes students’ religious practices and identity formation in Islamic primary education. Employing a qualitative approach with a case study design at SDIT Al-Marhamah Langsa, data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model, with validation through data triangulation. The findings reveal that the transformation produces a hybrid learning model that integrates dayah traditions into formal schooling through methodological simplification, curricular alignment, and contextualization of values. This process contributes to more structured yet reflective religious practices among students and fosters an adaptive form of religious identity within their social environment. The study underscores that transformation does not diminish the essence of tradition but rather reconfigures it into a more contextual and meaningful form in students’ lived experiences.